Focused Ultrasound Ablation of an Arteriovenous Malformation Model - Jones, Jesse; Bolding, Mark; Ullman, Henrik; Kaneko, Naoki; Tateshima, Satoshi (Frontiers in Neurology, 2021)
Brain AVMs are rare but serious vascular lesions that often pose a management dilemma between the risk of various treatment modalities and uncertain natural history during observation. We describe preliminary data on the use of focused ultrasound as a novel therapeutic strategy. In an AVM model, one session of ultrasound gradually reduced flow through the lesion without inducing rupture. Due to its noninvasive yet immediate ablative effects, focused ultrasound may allow safer treatment of AVMs. However, further studies are needed to clarify its efficacy and side effect profile.